2021
DOI: 10.1016/j.molmet.2021.101359
|View full text |Cite
|
Sign up to set email alerts
|

Exercise prevents fatty liver by modifying the compensatory response of mitochondrial metabolism to excess substrate availability

Abstract: Objective Liver mitochondria adapt to high-calorie intake. We investigated how exercise alters the early compensatory response of mitochondria, thus preventing fatty liver disease as a long-term consequence of overnutrition. Methods We compared the effects of a steatogenic high-energy diet (HED) for six weeks on mitochondrial metabolism of sedentary and treadmill-trained C57BL/6N mice. We applied multi-OMICs analyses to study the alterations in the proteome, transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 75 publications
2
4
0
Order By: Relevance
“…In this example, one striking observation is that not only metabolites—i.e., lipids—but also transcripts and proteins are generally upregulated in pathways related to lipid metabolism. This includes several pathways concerned with the metabolism of fatty acids, in agreement with the original study [HKK*21] and indicates that the increased amount of fatty acids supplied with the fat‐rich diet in the study caused an increased utilization of these in the abovementioned pathways. In contrast, individual proteins and transcripts assigned to the fatty acyl‐CoA biosynthesis pathway, i.e., a pathway concerned with the synthesis of fatty acids, showed a higher degree of downregulation.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In this example, one striking observation is that not only metabolites—i.e., lipids—but also transcripts and proteins are generally upregulated in pathways related to lipid metabolism. This includes several pathways concerned with the metabolism of fatty acids, in agreement with the original study [HKK*21] and indicates that the increased amount of fatty acids supplied with the fat‐rich diet in the study caused an increased utilization of these in the abovementioned pathways. In contrast, individual proteins and transcripts assigned to the fatty acyl‐CoA biosynthesis pathway, i.e., a pathway concerned with the synthesis of fatty acids, showed a higher degree of downregulation.…”
Section: Resultssupporting
confidence: 91%
“…This concludes the exemplary workflow on how a hypothesis can be generated using visMOP, which can then later be confirmed via different means. In this case we showed a tendency in the data which was previously analyzed in detail and published [HKK*21]. There are a multitude of different entry points for further detail analysis, e.g., other clusters focusing on other processes.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…It was shown that treadmill training modulates the increase in mitochondrial substrate oxidation in liver and skeletal muscle induced by a high-energy diet in mice, disconnecting it from pyruvate and acetyl CoA-driven lipid synthesis. This may help prevent the long-term deleterious effects of excessive nutritional intake on liver mitochondrial function and insulin sensitivity, thereby preventing the development of metabolic diseases such as fatty liver and NAFLD ( 269 ). As described in the mechanism section, intermittent hypoxia leads to disturbances in the gut microbiota-circulating exosome pathway, disrupting adipocyte homeostasis and leading to metabolic dysfunction manifested as IR, whereas experiments have shown that such changes can be attenuated by physical activity, as regular non-strenuous activity will lead to substantial improvements in the gut microbiota-exosome pathway ( 270 ).…”
Section: Treatment Of Irmentioning
confidence: 99%
“…Exercise is a powerful modulator of mitochondrial function and health in muscle 16 and liver 17 , an effect that is conserved across mouse, rat and human. Importantly, while concerted efforts have been made to understand the mitochondrial multi-omic response in one or two tissues 63,64 , this has not been undertaken at the scale or breadth of this work. We show that endurance exercise training activates a concerted mitochondrial response in multiple tissues, including the scarcely investigated colon and adrenal glands.…”
Section: Discussionmentioning
confidence: 99%